8g+5=-3(g+2)

Simple and best practice solution for 8g+5=-3(g+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8g+5=-3(g+2) equation:


Simplifying
8g + 5 = -3(g + 2)

Reorder the terms:
5 + 8g = -3(g + 2)

Reorder the terms:
5 + 8g = -3(2 + g)
5 + 8g = (2 * -3 + g * -3)
5 + 8g = (-6 + -3g)

Solving
5 + 8g = -6 + -3g

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '3g' to each side of the equation.
5 + 8g + 3g = -6 + -3g + 3g

Combine like terms: 8g + 3g = 11g
5 + 11g = -6 + -3g + 3g

Combine like terms: -3g + 3g = 0
5 + 11g = -6 + 0
5 + 11g = -6

Add '-5' to each side of the equation.
5 + -5 + 11g = -6 + -5

Combine like terms: 5 + -5 = 0
0 + 11g = -6 + -5
11g = -6 + -5

Combine like terms: -6 + -5 = -11
11g = -11

Divide each side by '11'.
g = -1

Simplifying
g = -1

See similar equations:

| y/10+5=-14 | | 2(4x-3)=(6x+4) | | x^2+1800=90x | | 2(3c-6)=5c+8 | | -6-7x+3x=38 | | 5=z+13 | | 8x-3(x-5)=2(x-4)+1 | | -4(3a+5)=-7(2a-5) | | 5(y-3)=3(2y-4) | | x/6+3=6-x/6 | | 3.4y=8.5 | | 6-(x-1)=8 | | 8x^3-y^3= | | 2(3x+2)=(2x-6)+2x | | 5Y-21=2Y | | 5(a-2)=3(4a-5) | | 6p-25=345 | | 3(2y-3)=5(y+1) | | 4(a-7)+4=2a-6 | | 2(x+4)+3=4+7+2x | | -2(3-4x)=7(x+2) | | 0.60x+0.05(12-x)=0.10(-71) | | 33=5v+3 | | 25n=525 | | 4u^3+2u^2-2u+1=0 | | 0.60x+0.05(12-z)=0.10(-71) | | 3y-11=25 | | 8-6d-3+7d=4 | | 3x+5-7-2x=3 | | -2k^2+3k+9=0 | | A+6=-3 | | 5y-3-4y=1 |

Equations solver categories